Structure-dependent regioselectivity of a roll-over cyclopalladation occuring at 2,2′-bipyridine-type ligands - Becker, Yanik; Schön, Florian; Becker, Sabine; Sun, Yu; Thiel, Werner R. (Journal of organometallic chemistry, 2021)
In this work, different bipyridine-analogue ligands bearing a dimethylamino group in the meta-position of one of the heterocyclic rings were synthesized and reacted with palladium(II) acetate under identical conditions. Cyclometallated palladium(II) complexes with C,N- or C,N,N’-coordinating chelate ligands are formed which were characterized by elemental analysis, 1H and 13C NMR spectroscopy, and single crystal X-ray diffraction analysis. In the case of the mononuclear, C,N,N’-coordinated complex, which is formed by an attack of the palladium(II) site at of the N-methyl groups, the primarily coordinating acetato ligand is exchanged against a chlorido ligand, which is liberated from the solvent dichloromethane by a nucleophilic substitution reaction. In contrast, cyclometallation occurring at one of the six-membered heterocycles leads to dinuclear acetato-bridged palladium(II) complexes.
Gesehen am 21.06.2021